X-Ray Beam-Width Limiting Device - Wasswa, William; Jager, Kylie de; Lester, John; Steiner, Stefan (Journal of Medical Devices, 2016)
The Lodox Statscan system (Fig. 1) utilizes an X-ray fan beam and employs linear slot-scanning radiography [1]. To precisely expose the region of interest with X-rays during scanning, the beam-width is collimated with sliders, driven on a toothed belt by servo motors, thereby adjusting the size of the slot through which the X-ray beam is transmitted. However, these sliders sometimes stall during horizontal C-arm scanning because of the effect of gravity and also often stop abruptly when they reach end of travel, which can damage the motors, the belt, or the sliders. Furthermore in the event of abrupt power supply loss while scanning, the current mechanism needs to be reinitialized in order to relocate the position of the beam-limiter blocks. The aim was therefore to develop an alternative X-ray beam-width limiting mechanism that is more reliable in both vertical and horizontal orientations, with soft stops should the.